Kingdom of Morocco : Accounting and Auditing - World Bank (Washington, DC, 2013)
This report provides an assessment of Moroccan accounting and auditing standards and practices, and the institutional capacity necessary to ensure high-quality financial reporting. The law gives accounting standard-setting responsibility to the National Accounting Council (Conseil National de la Comptabilité). Since the Council was established in 1989, Moroccan accounting standards have improved greatly. However, further progress is impeded by weaknesses in the accounting standard-setting process and, more so, by implementation issues. The Bank Al-Maghrib, Insurance and Social Welfare Directorate (Direction des Assurances et de la Prévoyance Sociales), and Securities Commission (Conseil Déontologique des Valeurs Mobilières) are responsible for monitoring the quality of financial information and the enforcement of accounting standards for credit institutions, insurance companies, and listed companies, respectively. While the Bank Al-Maghrib has established an institutional framework for bank monitoring that is more advanced than that of other sectors, the overall design and implementation of the three supervisory frameworks need improvement. The legislative framework for the Moroccan accounting profession is adequate. However, significant implementation issues exist, such as the absence of a quality assurance system and the lack of continuing professional education. Moroccan auditing standards are largely inspired by the International Standards on Auditing (IAS).However, the omission of certain standards weakens the Moroccan auditing framework. The large number of chartered accountants that do not even observe Moroccan auditing standards exacerbates this issue. While financial statements in Morocco generally include most of the information necessary to analyze the financial status of a company, certain lesser disclosure standards as compared to the IAS reduce the usefulness and transparency of Moroccan financial reports. Moreover, financial information is not readily available, as the mechanisms to publish statements are inefficient. The policy recommendations in this report focus on strengthening the enforcement of established accounting and auditing requirements, as well as supporting the initiatives that Morocco has been implementing over the last ten years.